Pedagogia histórico-crítica: o processo de construção e o perfil do currículo básico para a escola pública do Estado do Paraná (1980-1994). - Tonidandel, Sandra (2014)
This master's research in education has as its object of study inventorying the process of building the "Basic Curriculum for Public Schools of the State of Paraná" (CBEP) between 1980-1994 and assess how this Document, which was systematized along the 1980s and published in Parana, in December 1990, in fact expressed its commitment to Critical Pedagogy (PHC), as is widely reported. To cope with this problem, it was necessary to seize the mediations in the economic, social and political level to understand the real interests involved in promoting a differentiated education in the region. Thus, in Chapter I, the social context of the decade in 1970 is brought in, as it was the dictatorial period that produced the main reflections and criticisms of education and its current practice, whose discussions led to the systematization of educational counter-hegemonic theory to bourgeois pedagogies in the late 1970s and early 1980s, the PHC. In Chapter II, we contextualize the state of Paraná, socially, politically and economically. We address the political articulations, when the process of political opening, whose "consensus" of classes allowed, in late 1981, entering the initial formulations of PHC in the state, through the government of the PMDB candidate programs. Chapter III deals specifically with PHC, its construction process, its characteristics and peculiarities from 1980 to 1994. In Chapter IV, we discuss the construction process of CBEP and we explicit its characterization for in Concluding Remarks, returning to the starting point and answer which is the characteristic of this pedagogical proposal, seen as transformative in the state. The study documents for education in state of Parana, in the period between 1980-1994, showed that the state assumed as educational theory, whose proposal was understood as an expression of PHC at the level of common sense, and was a juxtaposition of opposing pedagogical proposals of which, by adjustment mechanism and negotiation with intellectuals of the working class also incorporated elements of PHC. However, the plurality of concepts present in the CBEP shows that the CHP is neither the prevailing theory in the design document. In this sense, a historical-critical curriculum is something yet to be built in the state of Paraná, then recovering the historical process of systematizing CBEP, and thereby establish the relationships that enable effective responses is part of the challenge of guiding possibilities and limitations in the construction of a transformative curriculum effectively.